I3O0-Type 3D Framework of Cobalt Cinnamate and Its Efficient Electrocatalytic Activity toward the Oxygen Evolution Reaction - Kang, Jaeun; Lee, Myung Jun; Oh, Nam Gue; Shin, Jiehye; Kwon, Seong Jung; Chun, Hyungphil; Kim, Seung Joo; Yun, Hoseop; Jo, Hongil; Ok, Kang Min; Do, Junghwan (Chemistry of Materials, 2021)
Designing metal-organic frameworks (MOFs) exhibiting fast charge and mass transport properties by utilizing their 3D network with permanent pores to facilitate electrolyte penetration into the active sites is a key challenge for the development of efficient electrocatalysts used for the oxygen evolution reaction (OER). Herein, we introduce an I3O0-type hybrid cobalt framework that functions as an efficient electrocatalyst for the OER. The structure contains a noninterpenetrated diamondoid Co-O-Co inorganic building block, which introduces unique helices and an extra-large intersecting Co36 ring channel. The unique 3D cobalt oxide framework decorated by π-conjugated t-cinnamate with the electron flexibility near Co centers and permanent pores with catalytic active sites results in good electrocatalytic activity toward the OER conducted in basic electrolytes. The observed overpotential of 361 mV at 10.0 mA cm-2 in 0.1 M KOH and a Tafel slop of 28 mV dec-1 are better than those of the reference materials.
Keywords: Building blockes; Catalytic active sites; Electrocatalytic activity; Electrolyte penetration; Metalorganic frameworks (MOFs); Oxygen evolution reaction (oer); Reference material; Ring channels